HR Process Automation and Its Impact on Employee Productivity and Job Satisfaction - Mia Andini; Sujoko Sujoko (PT. Anagata Sembagi Education, 2026)
The development of digital technology encourages organizations to adopt human resource process automation as a strategy to increase efficiency and competitiveness. HR automation not only has implications for improving work systems but also affects employee productivity and job satisfaction, indicators of organizational performance. This study aims to analyze the effect of HR process automation on employee productivity and job satisfaction. The research approach used a quantitative method with an explanatory survey design. Data were collected through questionnaires from 133 permanent employees in organizations that have implemented HR process automation, then analyzed using linear regression. The results show that HR process automation has a positive and significant effect on employee productivity. Automation also has a positive effect on job satisfaction, although with a more moderate effect. This finding indicates that automation affects performance aspects more quickly than work attitudes. The discussion of the research results shows that increased productivity is influenced by process efficiency and workflow clarity, while job satisfaction is influenced by perceptions of fairness, system transparency, and employee psychological experiences. This study confirms that HR automation is a socio-technical intervention that requires integration between technological efficiency and a humanistic approach to optimize its benefits sustainably